Candikuning Village Masterplan Based On Tourism - Ida Bagus Suryawan (Eduvest - Journal of Universal Studies, 2022)
The authentic characteristic of a village becomes the main tourism attraction that can be offered to tourists. Alternative tourism products are needed that can provide impetus for sustainable rural development and have management principles. Candi Kuning Village, which is part of the National Tourism Strategic Area, is one of the villages that is still able to survive in carrying out tourism services during the Covid 19 pandemic. This study aims to formulate a Master Plan as well as infrastructure development programs and other strategic infrastructures that are integrated between sectors, between spaces and between activities in one village area. The method used in this study uses a planning method consisting of a scoring method presented in the competitor matrix, a qualitative method for formulating an activity structure and SWOT. The results of the competitor matrix analysis show that the main competitors are Lake Buyan, tourist accommodation in the area, Agro Tourism and Culinary Tourism. The planning of the activity center is designed to be divided into 4 activity centers. The activity development plan in Candi Kuning Village consists of activities oriented to lake views, forest view orientation activities, development of local products (culinary and agro), utilization of community agricultural areas, environmental-based attractions and artificial attractions. The facilities developed are more for the appearance of the village, especially at the village border and activity center. This master plan is expected to strengthen the appearance of the village, increase tourism networks, increase the variety of income and self-motivation of the community in tourism services by local organizations.